2006
DOI: 10.1016/j.cell.2006.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PP2ACdc55 Phosphatase by Separase Initiates Mitotic Exit in Budding Yeast

Abstract: After anaphase, the high mitotic cyclin-dependent kinase (Cdk) activity is downregulated to promote exit from mitosis. To this end, in the budding yeast S. cerevisiae, the Cdk counteracting phosphatase Cdc14 is activated. In metaphase, Cdc14 is kept inactive in the nucleolus by its inhibitor Net1. During anaphase, Cdk- and Polo-dependent phosphorylation of Net1 is thought to release active Cdc14. How Net1 is phosphorylated specifically in anaphase, when mitotic kinase activity starts to decline, has remained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
371
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(395 citation statements)
references
References 53 publications
22
371
0
2
Order By: Relevance
“…In addition, we envision the approach to be beneficial in characterizing the cross-talk between phosphorylation and apoptotic proteolysis by including either phosphorylation mimetic or nonphosphorylatable residues in the TevS allele series (40,41). The approach outlined with the PTGR and SNIPer technology may prove particularly beneficial in profiling site-specific proteolysis throughout cell biology: for example, during cell-cycle progression mediated by separase during anaphase (42), differentiation, and intercellular signaling by Notch proteolysis (43), and mediating the unfolded protein response by ATF6 proteolysis (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we envision the approach to be beneficial in characterizing the cross-talk between phosphorylation and apoptotic proteolysis by including either phosphorylation mimetic or nonphosphorylatable residues in the TevS allele series (40,41). The approach outlined with the PTGR and SNIPer technology may prove particularly beneficial in profiling site-specific proteolysis throughout cell biology: for example, during cell-cycle progression mediated by separase during anaphase (42), differentiation, and intercellular signaling by Notch proteolysis (43), and mediating the unfolded protein response by ATF6 proteolysis (44).…”
Section: Discussionmentioning
confidence: 99%
“…In budding yeast, PP2A has also been implicated in regulating mitotic exit and the spindle orientation checkpoint (Queralt et al 2006;Wang and Ng 2006;Chan and Amon 2009). Studies in other systems have reported that some forms of PP2A are inactivated to permit entry into mitosis and that these are important subsequently for mitotic exit (Barr et al 2011).…”
Section: Pp2a and Sin Signalingmentioning
confidence: 99%
“…Because the FEAR controls Cdc14 release by inhibiting PP2A Cdc55 (9), the FEAR pathway is hyperactive in cdc55⌬ mutants, wherein the B-regulatory subunit of PP2A is deleted (7,8). To further confirm that CLB5 overexpression is toxic to FEAR mutants, we examined the growth of FEAR mutants overexpressing CLB5 in the absence of Cdc55.…”
Section: Fear Mutants Are More Sensitive To High Levels Of Clb5mentioning
confidence: 99%